Assessing the communication needs of parents of children with cancer - semantic, grammatical and psychological analyses - Nita, Elisabeta; Jianu, Maria-Magdalena (Swedish Journal of Romanian Studies, 2023)
The objective of the present study is to evaluate the communication needs of the parents of children with cancer from the perspective of the semantic values of the morphological units used and integrated into sentence structures or sentence segments (with response status to open questions) and from the perspective of the factual analysis of the percentages of closed questions. We believe that the results we have reached, processed with interdisciplinary tools of psycholinguistics, morphology, syntax and semantics of the Romanian language and psychological analysis, can provide data that can contribute to the identification of the best strategies for ensuring emotional well-being and increasing the quality of life of families where there is a child with cancer.